Inhibitory effect of panaxytriol on BV-2 microglial cell activation - Genki Hiramatsu; Daisuke Uta; Kenichi Mihara; Tsugunobu Andoh; Toshiaki Kume (Elsevier, 2021)
Activated microglia induce brain inflammation and neuronal death. Panaxytriol, ((3R,9R,10R)-Heptadec-1-en-4,6-diyne-3,9,10-triol), is a component of Panax ginseng C. A. Meyer extracts and activates the Nrf2-ARE signaling pathway. However, little is known about its effects on activated microglia in the brain. In this study, we investigated the effect of panaxytriol on lipopolysaccharide (LPS)-induced activated microglia in BV-2 cells. Panaxytriol suppressed LPS-induced NO production and inhibited the increase in iNOS protein expression in BV-2 cells. Besides, panaxytriol inhibited the mRNA expression of proinflammatory cytokines such as TNF-α, IL-1β, and IL-6. The inhibitory effect of panaxytriol on microglia activation did not affect the Nrf2-ARE pathway and the MAPK pathway. However, panaxytriol suppressed LPS-induced NF-κB nuclear translocation. These results suggest that panaxytriol inhibits the LPS-induced activation of microglia via the inhibition of NF-κB signaling pathway.